Using of Organic or Inorganic Fertilizers to Grow Thai Jasmine Rice 105 in Soil with Natural Radioactivity (226Ra, 232Th and 40K); Transfer of Radioactivity to Roots - chonlada raikham, chonlada (Food Agricultural Sciences and Technology, 2020)
This research study the radioactivity concentration of 226Ra, 232Th and 40K using organic and inorganic fertilizers were successfully measured as gamma ray spectrometry technique with HPGe detector on Thai Jasmine rice 105 plant (root) and on corresponding soil samples. Soil sample and natural water source of chemical characteristics (pH, OM, K, P and N) were also analyzed for their estimated effects on distribution of radioactivity concentration. The result of chemical characteristics showed that the pH of soil sample of organic and inorganic fertilizers before planting is acids in a range of 3.74-3.77 and the pH of natural water source is weak acids as 5.69±0.02. Result of organic matter found that the OM, N, P and K of soil in all fertilizer is in a range of 1.26±0.02-1.35±0.02, 0.0895±0.0025, 3 ppm and 54 ppm, respectively. Result of distribution of radioactivity concentration of 226Ra, 232Th and 40K found that soil sample before planting is relatively little value in both of fertilizers. The concentrations of 226Ra, 232Th and 40K for Soil of organic fertilizer farm were 26.72 ± 0.66, 11.24 ± 0.51 and 103.26 ± 3.93, respectively. The concentrations of 226Ra, 232Th and 40K for soil of inorganic fertilizer farm were 18.50 ± 0.56, 8.82 ± 0.41 and 63.30 ± 2.81, respectively. However, when using the organic fertilizer for planting found that it effects on radioactivity concentration of 40K which has higher value than that inorganic fertilizer for planting. While radioactivity concentration of 226Ra and 232Th is slightly change value in both of fertilizers. Using the organic and inorganic fertilizer planting resulted in uptake of radioactivity concentration from soil to root (TF) showed that the distribution radioactivity concentration of 40K uptake was higher than that of 226Ra and 232Th in all fertilizer planting.